Experimental investigation of visuali zation methods of earth quake catalogue maps - Pődor, Andrea; Kiszely, Marta (Geodesy and Cartography, 2014)
The aim of the study is to find possible solutions to represent earthquake catalogue data and design maps which can help non-professionals to identify those places where earthquakes occurred frequently. The goal is to visualize all available catalogue data sets in a complex way on a single map, displaying the long-term recurrence times of earthquakes. Therefore, raw data and aggregated data were combined with different cartographic visualization techniques to test the applicability of earthquake maps. Preliminary research demonstrates that aggregation can improve the process of retrieving information from earthquake maps and 3D visualization is useful to find the places of earthquakes of highest magnitude. A second result is that 3D visualization is not effective in the comparison of quantities of released energy and the number of earthquakes.